Bank Competition for Wholesale Funding: Evidence from Corporate Deposits - Florian Balke; Inaki Aldasoro; Andreas Barth; Egemen Eren (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
When banks are faced with a funding shortage in money market wholesale funding, they partly substitute by tapping other wholesale funding sources. Using auction-level data on large corporate deposits, we trace these substitution effects and their implications, which go beyond the balance sheets of banks affected by the funding shortage. Banks which are forced to seek alternative funding sources ("affected" banks) crowd out other initially unaffected banks, which pay substantially more to retain funding. Affected banks achieve funding substitution mostly through an intensive margin adjustment, increasing their share of funding coming from stable funding providers. We document a mechanism to explain this observation, building on the existence of a pecking order of funding in fragmented markets and the matching of banks' and firms' preferences. The crowding-out of initially unaffected banks worsens their pool of funding providers. The stock prices of these banks underperform those of affected banks, while CDS spreads remain unchanged between the two groups. Our results suggest that crowding out in funding markets affect competitiveness on the asset side.
Keywords: G21; G28; 330; global banks; dollar funding; US money market fund reform; corporate deposits